Difficulty acquiring accurate and rapid information regarding the blood oxygen saturation in patients under vasoconstriction (2018)
"The measurement of oxygen saturation in patients is one of the procedures that medical personnel must perform as part of international protocols. However, the current use pulse oximeter presents 3 main difficulties encountered from field work in ambulances and emergency medical care centers. First, it can only be located in peripheral areas such as fingers and lobe of the ear so it can not measure quickly and accurately when there is low blood perfusion. Secondly, it is uncomfortable for the patient and additionally, it is unstable. The pathological consequences of inadequate ventilation are, on the one hand, hypoxia, that the supplement is lower than the oxygen required and results in inadequate perfusion of oxygen to vital organs. On the other hand, there is hyperoxia that is to supply more oxygen than required. Patients with hyperoxia had higher mortality in the hospital (29.7%), in terms of normoxia (19.4%) and hypoxia (13.2%). This implies damage to the central nervous system, lungs, embolisms and decreased cardiac output [1]. In view of the above, an oxygen saturation measurement system is designed for patients in the state of vasoconstriction, which offers stability, comfort, precision and rapid measurement of oxygen saturation by means of a sensor that can be attached to different parts of the body that work with the patient. transmittance phenomenon. Now, when performing tests where the behavior between this product and the current use pulse oximeter was compared, an error of approximately 3% was obtained, which was made by means of an established protocol. Finally, the designed system proves a robust alternative for measuring oxygen saturation in all contexts, even under vasoconstriction conditions."--Tomado del Formato de Documento de Grado